Thiol-functionalized 1,2,4-triazolium salt as carbene ligand precursor - Seitz, Stefanie Christine; Rominger, Frank; Straub, Bernd Franz (Journal of organometallic chemistry, 2012)
Abstract: A thiol-functionalized 1,2,4-triazolylidene ligand precursor salt was synthesized from 2-(4-methoxybenzylthio)aniline. Removal of the protecting group under strongly acidic conditions (trifluoroacetic acid/trifluoromethanesulfonic acid) yielded a 1,2,4-triazolium salt comprising a free thiophenol moiety as was confirmed by X-ray analysis. The fairly air-stable thiophenol was oxidized by DMSO resulting in ring closure to a benzothiazole. Deprotonation and metalation resulted in the cis- and trans-isomers of the square-planar bis(NHC-thiolato) Ni(II), Pd(II) and Pt(II) complexes. The palladium complex was successfully employed as catalyst in C–C, C–N and C–S cross-coupling reactions. Chlorobenzene was activated only in the amination reaction. Cobalt dichloride formed an octahedral Co(III) complex under oxidation of the metal center. A η3−allyldicarbonylmolybdenum(II) complex of the C,S-ligand was prepared.